Residual stress provides significant strengthening and ductility in gradient structured materials. Issue 11 (2nd November 2019) - Yang, Mu-Xin; Li, Run-Guang; Jiang, Ping; Yuan, Fu-Ping; Wang, Yan-Dong; Zhu, Yun-Tian; Wu, Xiao-Lei
ABSTRACT: Residual stress exists extensively in biological and engineering structures. Here we report that residual stress can be engineered to significantly enhance the strength and ductility of gradient materials. In-situ synchrotron experiments revealed that the strongest strain hardening occurred in the layer with the highest compressive residual stress in a gradient structure. This layer remained elastic longer than adjacent layers during tension, producing high hetero-deformation induced stress to increase strength and enhancing work hardening even after the disappearance of the compressive stress to increase ductility. This finding provides a new paradigm for designing gradient structures for superior mechanical properties. IMPACT STATEMENT: We show that compressive residual stress layer in SMAT-processed gradient material produces hetero-deformation induced hardening, which played a major role in improving strength and ductility. GRAPHICAL ABSTRACT: